Aged steel slag drainage asphalt mixture OGFC-10 and preparation method thereof

The f-CaO content is reduced by steel slag aging technology, and the aged steel slag drainage asphalt mixture OGFC-10 was prepared, which solved the problem of poor stability of steel slag and significantly improved its performance and application prospects in road materials.

CN119430745APending Publication Date: 2025-02-14JIANGSU SHAGANG STEEL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411785745.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Because steel slag contains more free calcium oxide (f-CaO), the stability of steel slag products mixed with steel slag is poor, limiting the large-scale application of steel slag in the field of road materials.

Method used

Through steel slag aging technology, the f-CaO content in the steel slag is reduced, and an aged steel slag drainage asphalt mixture OGFC-10 was prepared. The composition distribution ratio includes no more than 3mm limestone, 3-15mm aged converter tailings, 3-5mm basalt, 5-10mm basalt, 5-10mm aged electric furnace tailings, limestone ore powder and SBS modified asphalt.

Benefits of technology

The dynamic stability, bending strain, residual stability, freeze-thaw splitting strength ratio, friction coefficient, water seepage coefficient and durability of steel slag in asphalt mixture are improved, and its application prospects and environmental benefits in road engineering are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005173991940000081
    Figure BDA0005173991940000081
Patent Text Reader

Abstract

The invention discloses an aged steel slag drainage asphalt mixture OGFC-10 and a preparation method thereof, and belongs to the technical field of steel slag resource utilization. Through the steel slag aging technology, the content of f-CaO in the converter tailings and the electric furnace tailings is reduced, the limitation that the content of f-CaO in the steel slag is high is broken through, and the steel slag is used for preparing the drainage asphalt mixture OGFC-10; the aged steel slag drainage asphalt mixture OGFC-10 is prepared from limestone not exceeding 3 mm, aged converter tailings not exceeding 5 mm, basalt 3-5 mm, basalt 5-10 mm, aged electric furnace tailings 5-10 mm, limestone mineral powder and SBS modified asphalt. The pavement performance test result of the obtained product shows that the material dynamic stability, the bending strain, the residual stability, the freeze-thaw splitting strength ratio, the friction coefficient and the water seepage coefficient of the drainage asphalt mixture doped with the aged steel slag are improved compared with those of the drainage asphalt mixture doped with the unaged steel slag, and the drainage asphalt mixture has wide application prospects and important environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel slag resource utilization, and in particular to an aged steel slag drainage asphalt mixture OGFC-10 and a preparation method thereof. Background Art

[0002] With the rapid development of the steel industry, how to properly dispose of the solid waste steel slag generated in the steelmaking process has become an urgent problem to be solved in the steel industry. The contradiction between the high output and low utilization rate of steel slag has attracted widespread attention in the steel industry, and relevant experts have carried out a lot of research. Since quicklime needs to be added during the steelmaking process, the steel slag contains a large amount of free calcium oxide (f-CaO), which makes the stability of steel slag products mixed with steel slag poor, limiting the large-scale application of steel slag in the field of road materials.

[0003] At the same time, due to the rapid development of road construction, natural stone resources for roads are increasingly scarce and their prices are high. Steel slag has physical and mechanical properties, application prospects and environmental benefits that are superior to natural stone for roads, and can be used as a new type of road building material in road engineering construction. At present, most urban roads use dense graded asphalt mixtures, which have the disadvantages of low pavement porosity and poor drainage. When vehicles are driving on rainy days, water mist and slippage are prone to occur, which may cause safety accidents. Drainage asphalt mixtures have the characteristics of large porosity and rough surface, good drainage and anti-skid performance, which can significantly improve the driving conditions of vehicles on rainy days, reduce the dangers caused by water mist and vehicle slippage, and reduce the probability of traffic accidents. Summary of the invention

[0004] Technical problems to be solved: In view of the problem in the prior art that the steel slag contains a large amount of free calcium oxide (f-CaO), which makes the stability of the steel slag products mixed with steel slag poor, limiting the large-scale application of steel slag in the field of road materials, the present invention proposes an aged steel slag drainage asphalt mixture OGFC-10 and a preparation method thereof. Through the steel slag aging technology, the f-CaO content in the steel slag is reduced, breaking the limitation of the high f-CaO content in the steel slag. The road performance test results show that the dynamic stability, bending strain, residual stability, freeze-thaw splitting strength ratio, friction coefficient, and water permeability coefficient of the drainage asphalt mixture mixed with aged steel slag are all improved compared with those mixed with unaged steel slag, and it has broad application prospects and important environmental benefits.

[0005] Technical solution: One of the purposes of the present invention is to provide a method for preparing aged steel slag drainage asphalt mixture OGFC-10, the steps are as follows:

[0006] Step 1, prepare aged steel slag, take converter tailings and electric furnace tailings and put them into different water pools, control the water temperature at 45-55°C for 8 hours, then take out the soaked tailings, transfer them to a constant temperature and humidity curing box, control the temperature at 45-55°C and the humidity at 85-95%, and keep the curing box continuously ventilated with air, dry them after aging for 90 days, and sieve them to obtain aged converter tailings not exceeding 5 mm and aged electric furnace tailings of 5-10 mm respectively;

[0007] Step 2, designing the proportion of aged steel slag drainage asphalt mixture OGFC-10, the component proportion of aged steel slag drainage asphalt mixture OGFC-10 is as follows: 5-7 parts by mass of limestone not exceeding 3mm, 3-15 parts by mass of aged converter tailings not exceeding 5mm, 28-40 parts by mass of 3-5mm basalt, 10-25 parts by mass of 5-10mm basalt, 25-37 parts by mass of 5-10mm aged electric furnace tailings, 2-4 parts by mass of limestone powder and 4.0-4.4 parts by mass of SBS modified asphalt. Except for SBS modified asphalt, the other components use 2.36mm sieve hole pass rate as the key sieve hole of aged steel slag drainage asphalt mixture OGFC-10, and the gradation design is carried out with a 2.36mm sieve hole pass rate of 14-16%;

[0008] Step 3, prepare aged steel slag drainage asphalt mixture OGFC-10, put limestone not exceeding 3mm, aged converter tailings not exceeding 5mm, 3-5mm basalt, 5-10mm basalt, 5-10mm aged electric furnace tailings, and limestone powder into an oven for drying according to the designed amount; put SBS modified asphalt into an oven for heating and softening; put limestone not exceeding 3mm, 3-5mm basalt, and 5-10mm basalt into a mixing pot for heating and mixing; pour aged converter tailings not exceeding 5mm and aged electric furnace tailings of 5-10mm into a mixing pot for heating and mixing; pour limestone powder into a mixing pot for heating and mixing; pour SBS modified asphalt into a mixing pot according to the designed amount for heating and mixing; then pour out the evenly mixed OGFC-10 aged steel slag drainage asphalt mixture to form an asphalt mixture specimen.

[0009] Preferably, the free calcium oxide content of the aged converter tailings and the aged electric furnace tailings in step 1 is less than 3%.

[0010] Preferably, the particle size of the converter tailings is no more than 5 mm, and the particle size of the electric furnace tailings is 5-10 mm.

[0011] Preferably, the grading design in the step 2 is as follows: the pass rate of 13.2mm sieve hole is 100%; the pass rate of 9.5mm sieve hole is 90% to 100%; the pass rate of 4.75mm sieve hole is 50% to 70%; the pass rate of 2.36mm sieve hole is 10% to 22%; the pass rate of 1.18mm sieve hole is 6% to 18%; the pass rate of 0.6mm sieve hole is 4% to 15%; the pass rate of 0.3mm sieve hole is 3% to 12%; the pass rate of 0.15mm sieve hole is 3% to 8%; the pass rate of 0.075mm sieve hole is 2% to 6%.

[0012] Preferably, in the step three, limestone not exceeding 3 mm, aged converter tailings not exceeding 5 mm, basalt not exceeding 3-5 mm, basalt not exceeding 5-10 mm, aged electric furnace tailings, and limestone powder are placed in an oven for drying according to the designed amount, the temperature is 105 ° C, and the time is 2 h; the SBS modified asphalt is placed in an oven for heating and softening, the heating temperature is set to 165 ° C, and the time is 2 h; limestone not exceeding 3 mm, basalt not exceeding 3-5 mm, basalt not exceeding 5-10 mm, and basalt not exceeding 3 mm are placed in an oven for heating and softening, and the heating temperature is set to 165 ° C, and the time is 2 h. Pour the mixed slag into the mixing pot and heat and mix it for 15 seconds, and set the temperature of the mixing pot to 165°C; pour the aged converter tailings not exceeding 5mm and the aged electric furnace tailings of 5-10mm into the mixing pot and heat and mix it for 20 seconds, and set the temperature of the mixing pot to 165°C; pour the limestone ore powder into the mixing pot and heat and mix it for 5 seconds, and set the temperature of the mixing pot to 165°C; pour the SBS modified asphalt into the mixing pot according to the designed amount and heat and mix it for 60 seconds, and set the temperature of the mixing pot to 165°C.

[0013] Another object of the present invention is to provide an aged steel slag drainage asphalt mixture OGFC-10 prepared based on the above method.

[0014] Beneficial effects:

[0015] (1) Aged steel slag has more carbonates and silicates, which improves the strength and wear resistance of steel slag, making the asphalt mixture more resistant to repeated rolling and wear caused by rutting. Aged steel slag has better angularity and surface texture, which improves the interlocking effect between steel slag and steel slag, and between steel slag and aggregate, thereby increasing the internal friction of the asphalt mixture. In addition, the alkalinity of steel slag is relatively high, which will chemically react with weakly acidic asphalt to form a more stable cementing phase, thus improving the high temperature stability of the aged steel slag asphalt mixture.

[0016] (2) The particle morphology, surface roughness and pore structure of aged steel slag have been improved, which increases the adhesion between steel slag and asphalt. When the asphalt mixture is subjected to bending stress, the contact interface between steel slag, aggregate and asphalt is not easily damaged, thereby improving the bending strain capacity. In addition, aged steel slag increases the overall stiffness of the asphalt mixture and maintains a certain degree of flexibility. This combination of rigidity and flexibility enables the asphalt mixture to better resist deformation when subjected to bending stress and improves the bending strain.

[0017] (3) The crystal structure of aged steel slag is stable, which reduces the expansion of microcracks and pores in the asphalt mixture, improves the overall stability of the asphalt mixture, and ensures that it reduces internal damage and maintains high strength during the freeze-thaw cycle. The f-CaO content in unaged steel slag is relatively high, and it is easy to expand in volume, which destroys the adhesion interface between steel slag and aggregate and asphalt, resulting in a decrease in the water stability of unaged steel slag drainage asphalt mixture.

[0018] (4) Aged steel slag has more microscopic protrusions and depressions, making its surface rougher and providing better friction when in contact with tires. Aged steel slag also has better angularity, which increases the bite force and friction between aggregates, allowing the mixture to generate greater resistance when the tires roll.

[0019] (5) Aged steel slag has stronger stability and is not easy to react with water, which can provide sufficient porosity and connected porosity. Unaged steel slag, on the other hand, has weaker stability and is prone to hydration and carbonation reactions when in contact with water, generating Ca(OH)2 and CaCO3, which cause the mixture to expand and crack. The fine particles that fall from the cracks are blocked in the voids, resulting in a weakened water permeability of the unaged steel slag drainage asphalt mixture.

[0020] (6) The f-CaO and f-MgO in aged steel slag are aged into minerals such as carbonates and hardly react after being soaked in water. However, unaged steel slag contains a small amount of f-CaO and f-MgO, which are very likely to undergo hydration and carbonation reactions after being soaked in water to generate CaCO3 and MgCO3, resulting in a higher water expansion rate of the asphalt mixture. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with specific embodiments.

[0022] Unless otherwise specified, the raw materials used in the examples of this specification are all from ordinary commercial products. Among them, converter tailings and electric furnace tailings are from the steel plant of Jiangsu Shagang Group Co., Ltd. The particle size of the converter tailings screened is no more than 5mm, and the particle size range of the electric furnace tailings is 5-10mm. After testing, the f-CaO content in the converter tailings not exceeding 5mm and the electric furnace tailings of 5-10mm is 3.8% and 3.2% respectively, which does not meet the requirement of no more than 3% in the "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004), and cannot be directly used as road engineering materials. Aging treatment is required to reduce its f-CaO content to meet the requirements of the specifications.

[0023] The main components of converter tailings and electric furnace tailings are as follows:

[0024] CaO Fe <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO MnO <![CDATA[TiO2]]> <![CDATA[P2O5]]> f-CaO Converter slag 46.9% 15.3% 15.4% 1.4% 8.6% 2.9% 1.1% 3.0% 3.8% Electric furnace slag 25.4% 34.2% 13.5% 3.0% 5.1% 4.6% 0.8% 1.0% 3.2%

[0025] Limestone powder was purchased from Jiangsu Kamei Mining Co., Ltd.;

[0026] Limestone not exceeding 3 mm was purchased from Jiangsu Kamei Mining Co., Ltd.;

[0027] 3-5 mm basalt was purchased from Jiangsu Kamei Mining Co., Ltd.;

[0028] 5-10 mm basalt was purchased from Jiangsu Kamei Mining Co., Ltd.;

[0029] The model of SBS modified asphalt is SBS (ID), which was purchased from Aeruifu (Shanghai) New Material Technology Co., Ltd.

[0030] Example

[0031] The present invention provides a method for preparing aged steel slag drainage asphalt mixture OGFC-10, comprising the following steps:

[0032] Step 1: Preparation of aged steel slag, specifically comprising the following steps:

[0033] Step 1-1: Use slag aging technology to reduce the f-CaO content in converter tailings and electric furnace tailings. Take a certain amount of converter tailings not exceeding 5mm and electric furnace tailings of 5-10mm, put them into two different water pools, slowly add water to the two water pools, insert heating rods at the same time, control the water temperature to maintain at 50±5℃, and continue for 8 hours;

[0034] Step 1-2: Take out the converter tailings not exceeding 5mm and the electric furnace tailings of 5-10mm after soaking for 8 hours, and move them into a constant temperature and humidity curing box, control the temperature at 50±5℃ and the humidity at 90±5%, and keep the curing box continuously ventilated, and the aging lasts for a total of 90 days;

[0035] Step 1-3: Dry the aged converter tailings not exceeding 5 mm and electric furnace tailings of 5-10 mm, and re-screen them to obtain aged converter tailings not exceeding 5 mm and aged electric furnace tailings of 5-10 mm. The f-CaO contents are measured to be 2.4% and 2.3% respectively, which meet the requirement of "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004) of not more than 3%, and can be used as aggregates for asphalt mixtures.

[0036] Step 2: Mix design of slag drainage asphalt mixture OGFC-10

[0037] The 2.36 mm sieve hole pass rate was used as the key sieve hole of the steel slag drainage asphalt mixture OGFC-10, and the initial gradation was designed with a 2.36 mm sieve hole pass rate of 15% ± 1%.

[0038] The details are as follows:

[0039] Step 2-1: Design the material composition of the steel slag drainage asphalt mixture OGFC-10 by mass as follows:

[0040] Limestone not exceeding 3mm: 5-7 parts.

[0041] Aged converter tailings not exceeding 5mm: 3-15 parts.

[0042] 3-5mm basalt: 28-40 parts.

[0043] 5-10mm basalt: 10-25 parts.

[0044] 5-10mm aged electric furnace tailings: 25-37 parts.

[0045] Limestone powder: 2-4 parts.

[0046] SBS modified asphalt: 4.0-4.4 parts

[0047] Step 2-2: The synthetic gradation of the raw materials of steel slag drainage asphalt mixture OGFC-10, except SBS modified asphalt, must meet the following sieve pass rate:

[0048] The pass rate of 13.2mm sieve hole is 100%; the pass rate of 9.5mm sieve hole is 90%~100%; the pass rate of 4.75mm sieve hole is 50%~70%; the pass rate of 2.36mm sieve hole is 10%~22%; the pass rate of 1.18mm sieve hole is 6%~18%; the pass rate of 0.6mm sieve hole is 4%~15%; the pass rate of 0.3mm sieve hole is 3%~12%; the pass rate of 0.15mm sieve hole is 3%~8%; the pass rate of 0.075mm sieve hole is 2%~6%.

[0049] Step 3: Preparation of slag-drained asphalt mixture OGFC-10

[0050] Step 3-1: Put limestone not exceeding 3mm, aged converter tailings not exceeding 5mm, 3-5mm basalt, 5-10mm basalt, 5-10mm aged electric furnace tailings, and limestone powder into an oven, set the temperature to 105°C, and the drying time for 2 hours.

[0051] Step 3-2: Place the SBS modified asphalt in an oven and set the temperature to 165°C for 2 hours.

[0052] Step 3-3: Put limestone not exceeding 3mm, basalt of 3-5mm and basalt of 5-10mm into the mixing pot, stir for 15s, and set the mixing pot temperature to 165℃.

[0053] Step 3-4: Pour aged converter tailings not exceeding 5mm and aged electric furnace tailings of 5-10mm into the mixing pot, stir for 20s, and set the mixing pot temperature to 165℃.

[0054] Step 3-5: Pour the limestone powder into the mixing pot, stir for 5 seconds, and set the mixing pot temperature to 165°C.

[0055] Step 3-6: Pour SBS modified asphalt into the mixing pot, stir for 60 seconds, and set the mixing pot temperature to 165°C.

[0056] Step 3-7: pour out the evenly mixed OGFC-10 asphalt mixture, and it can be used for construction pouring. In the examples and comparative examples of this specification, Marshall specimens and rutting plate specimens are formed respectively. The forming methods of Marshall specimens and rutting plate specimens are carried out with reference to T 0702-2011 Asphalt mixture specimen preparation method (compaction method) and T 0703-2011 Asphalt mixture specimen preparation method (wheel rolling method) in the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011).

[0057] Example 1

[0058] The difference is that the ratio of the steel slag drainage asphalt mixture OGFC-10 in this embodiment is as follows: weigh 5 parts of limestone not exceeding 3 mm, 15 parts of aged converter tailings not exceeding 5 mm, 28 parts of 3-5 mm basalt, 25 parts of 5-10 mm basalt, 25 parts of 5-10 mm aged electric furnace tailings, 2 parts of limestone powder, and 4 parts of SBS modified asphalt. According to step 3, the Marshall specimen and the rutting plate specimen are formed.

[0059] The sieve pass rates of the synthetic grading in step 2-2 are as follows: 13.2mm sieve pass rate is 100%; 9.5mm sieve pass rate is 98.6%; 4.75mm sieve pass rate is 52.8%; 2.36mm sieve pass rate is 16.2%; 1.18mm sieve pass rate is 12.2%; 0.6mm sieve pass rate is 8.5%; 0.3mm sieve pass rate is 6.3%; 0.15mm sieve pass rate is 5.2%; 0.075mm sieve pass rate is 4.4%.

[0060] Example 2

[0061] The difference is that the ratio of the steel slag drainage asphalt mixture OGFC-10 in this embodiment is as follows: weigh 7 parts of limestone not exceeding 3 mm, 7 parts of aged converter tailings not exceeding 5 mm, 40 parts of 3-5 mm basalt, 10 parts of 5-10 mm basalt, 33 parts of 5-10 mm aged electric furnace tailings, 3 parts of limestone powder, and 4.2 parts of SBS modified asphalt. According to step 3, the Marshall specimen and the rutting plate specimen are formed.

[0062] The sieve hole pass rate of the synthetic gradation in step 2-2 is as follows: 13.2mm sieve hole pass rate is 100%; 9.5mm sieve hole pass rate is 98.1%; 4.75mm sieve hole pass rate is 55.8%; 2.36mm sieve hole pass rate is 15.2%; 1.18mm sieve hole pass rate is 11.6%; 0.6mm sieve hole pass rate is 8.5%; 0.3mm sieve hole pass rate is 6.8%; 0.15mm sieve hole pass rate is 5.8%; 0.075mm sieve hole pass rate is 4.8%.

[0063] Example 3

[0064] The difference is that the ratio of the steel slag drainage asphalt mixture OGFC-10 in this embodiment is as follows: weigh 7 parts of limestone not exceeding 3 mm, 3 parts of aged converter tailings not exceeding 5 mm, 39 parts of 3-5 mm basalt, 10 parts of 5-10 mm basalt, 37 parts of 5-10 mm aged electric furnace tailings, 4 parts of limestone powder, and 4.4 parts of SBS modified asphalt. According to step 3, the Marshall specimen and the rutting plate specimen are formed.

[0065] The sieve hole pass rate of the synthetic gradation in step 2-2 is as follows: 13.2mm sieve hole pass rate is 100%; 9.5mm sieve hole pass rate is 97.9%; 4.75mm sieve hole pass rate is 52.0%; 2.36mm sieve hole pass rate is 14.2%; 1.18mm sieve hole pass rate is 11.2%; 0.6mm sieve hole pass rate is 8.6%; 0.3mm sieve hole pass rate is 7.3%; 0.15mm sieve hole pass rate is 6.4%; 0.075mm sieve hole pass rate is 5.6%.

[0066] Comparative Example 1

[0067] The difference is that this comparative example does not use aged steel slag, and the mass proportion of the drainage asphalt mixture OGFC-10 in step 2 is designed as follows: weigh 10 parts of limestone not exceeding 3 mm, 55 parts of 3-5 mm basalt, 32 parts of 5-10 mm basalt, 3 parts of limestone powder, and 4.2 parts of SBS modified asphalt. According to step 3, the Marshall specimen and the rutting plate specimen are formed.

[0068] The sieve hole pass rate of the synthetic gradation in step 2-2 is as follows: 13.2mm sieve hole pass rate is 100%; 9.5mm sieve hole pass rate is 100%; 4.75mm sieve hole pass rate is 69.0%; 2.36mm sieve hole pass rate is 16.1%; 1.18mm sieve hole pass rate is 12.2%; 0.6mm sieve hole pass rate is 9.1%; 0.3mm sieve hole pass rate is 7.6%; 0.15mm sieve hole pass rate is 6.5%; 0.075mm sieve hole pass rate is 5.8%.

[0069] Comparative Example 2

[0070] The difference is that this comparative example uses aged converter tailings instead of electric furnace tailings, and the mass proportion of the drainage asphalt mixture OGFC-10 in step 2 is designed as follows: weigh 10 parts of limestone not exceeding 3 mm, 11 parts of aged converter tailings not exceeding 5 mm, 45 parts of 3-5 mm basalt, 32 parts of 5-10 mm basalt, 2 parts of limestone powder, and 4.2 parts of SBS modified asphalt. According to step 3, the Marshall specimen and the rutting plate specimen are formed.

[0071] The sieve pass rates of the synthetic gradation in step 2-2 are as follows: 13.2 mm sieve pass rate is 100%; 9.5 mm sieve pass rate is 100%; 4.75 mm sieve pass rate is 69.8%; 2.36 mm sieve pass rate is 19.9%; 1.18 mm sieve pass rate is 14.8%; 0.6 mm sieve pass rate is 10.2%; 0.3 mm sieve pass rate is 7.7%; 0.15 mm sieve pass rate is 6.2%; 0.075 mm sieve pass rate is 5.3%.

[0072] Comparative Example 3

[0073] The difference is that this comparative example uses aged electric furnace tailings instead of converter tailings, and the mass proportion of the drainage asphalt mixture OGFC-10 in step 2 is designed as follows: weigh 8 parts of limestone not exceeding 3 mm, 42 parts of 3-5 mm basalt, 10 parts of 5-10 mm basalt, 38 parts of 5-10 mm aged electric furnace tailings, 2 parts of limestone powder, and 4.2 parts of SBS modified asphalt. According to step 3, the Marshall specimen and the rutting plate specimen are formed.

[0074] The sieve hole pass rates of the synthetic gradation in step 2-2 are as follows: 13.2mm sieve hole pass rate is 100%; 9.5mm sieve hole pass rate is 97.8%; 4.75mm sieve hole pass rate is 50.8%; 2.36mm sieve hole pass rate is 11.8%; 1.18mm sieve hole pass rate is 8.9%; 0.6mm sieve hole pass rate is 6.4%; 0.3mm sieve hole pass rate is 5.2%; 0.15mm sieve hole pass rate is 4.4%; 0.075mm sieve hole pass rate is 3.7%.

[0075] Comparative Example 4

[0076] The difference is that this comparative example uses unaged converter tailings and electric furnace tailings, and the mass proportion of the drainage asphalt mixture OGFC-10 in step 2 is designed as follows: weigh 7 parts of limestone not exceeding 3mm, 10 parts of unaged converter tailings not exceeding 5mm, 35 parts of 3-5mm basalt, 10 parts of 5-10mm basalt, 35 parts of 5-10mm unaged electric furnace tailings, 3 parts of limestone powder, and 4.2 parts of SBS modified asphalt. According to step 3, the Marshall specimen and the rutting plate specimen are formed.

[0077] The sieve hole pass rates of the synthetic gradation in step 2-2 are as follows: 13.2mm sieve hole pass rate is 100%; 9.5mm sieve hole pass rate is 98.0%; 4.75mm sieve hole pass rate is 54.3%; 2.36mm sieve hole pass rate is 16.4%; 1.18mm sieve hole pass rate is 12.5%; 0.6mm sieve hole pass rate is 9.0%; 0.3mm sieve hole pass rate is 7.0%; 0.15mm sieve hole pass rate is 5.9%; 0.075mm sieve hole pass rate is 5.1%.

[0078] The road performance of steel slag drainage asphalt mixture is a key factor to measure the impact of steel slag on its performance. It not only reflects the adaptability and durability of the material in a complex traffic environment, but is also directly related to the overall quality and service life of the road project. The road performance includes high temperature stability, low temperature crack resistance, water stability, anti-skid performance, drainage performance, and durability. Among them, dynamic stability is a key parameter for evaluating the high temperature stability of steel slag drainage asphalt mixture; bending strain is a key parameter for evaluating the low temperature crack resistance of steel slag drainage asphalt mixture; residual stability and freeze-thaw splitting strength ratio are key parameters for evaluating the residual stability of steel slag drainage asphalt mixture; friction coefficient is a key parameter for evaluating the anti-skid performance of steel slag drainage asphalt mixture; water permeability coefficient is a key parameter for evaluating the drainage performance of steel slag drainage asphalt mixture; water immersion expansion rate is a key parameter for evaluating the durability of steel slag drainage asphalt mixture. The specific test results of Examples 1-3 and Comparative Examples are shown in Table 1.

[0079] The experimental method for high temperature stability test refers to T 0719-2011 asphalt mixture rutting test in "Test Code for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011); the experimental method for low temperature crack resistance test refers to T 0715-2011 asphalt mixture bending test in "Test Code for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011); the experimental method for water stability test refers to T 0709-2011 asphalt mixture Marshall stability test and T 0729-2000 asphalt mixture freeze-thaw splitting test in "Test Code for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011); the experimental method for anti-skid performance test refers to the pendulum friction test; the experimental method for drainage performance test refers to T 0715-2011 asphalt mixture bending test in "Test Code for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011). 0730-2011 Asphalt mixture water permeability test; Durability test experimental method refers to "Steel slag stability test method" (GB / T24175-2009).

[0080] Table 1 Road performance test results

[0081]

[0082] It can be seen from Table 1 that the aged steel slag drainage asphalt mixture OGFC-10 designed in the present invention can effectively improve the road performance of the drainage asphalt mixture OGFC-10, and has comprehensive benefits in terms of technology, economy and environmental protection.

[0083] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned implementation modes, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned implementation modes can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the implementation modes of the present invention.

Claims

1. A method for preparing aged steel slag drainage asphalt mixture OGFC-10, characterized in that: Here are the steps: Step 1, prepare aged steel slag, take converter tailings and electric furnace tailings and put them into different water pools, control the water temperature at 45-55°C for 8 hours, then take out the soaked tailings, transfer them to a constant temperature and humidity curing box, control the temperature at 45-55°C and the humidity at 85-95%, and keep the curing box continuously ventilated with air, dry them after aging for 90 days, and sieve them to obtain aged converter tailings not exceeding 5 mm and aged electric furnace tailings of 5-10 mm respectively; Step 2, designing the mix ratio of aged steel slag drainage asphalt mixture OGFC-10, the component ratio of aged steel slag drainage asphalt mixture OGFC-10 is as follows: 5-7 parts by mass of limestone not exceeding 3mm, 3-15 parts by mass of aged converter tailings not exceeding 5mm, 28-40 parts by mass of 3-5mm basalt, 10-25 parts by mass of 5-10mm basalt, 25-37 parts by mass of 5-10mm aged electric furnace tailings, 2-4 parts by mass of limestone powder and 4.0-4.4 parts by mass of SBS modified asphalt. Except for SBS modified asphalt, the other components use 2.36mm sieve hole pass rate as the key sieve hole of aged steel slag drainage asphalt mixture OGFC-10, and the gradation design is carried out with a 2.36mm sieve hole pass rate of 14-16%; Step 3, prepare aged steel slag drainage asphalt mixture OGFC-10, put limestone not exceeding 3mm, aged converter tailings not exceeding 5mm, 3-5mm basalt, 5-10mm basalt, 5-10mm aged electric furnace tailings, and limestone powder into an oven for drying according to the designed amount; put SBS modified asphalt into an oven for heating and softening; put limestone not exceeding 3mm, 3-5mm basalt, and 5-10mm basalt into a mixing pot for heating and mixing; pour aged converter tailings not exceeding 5mm and aged electric furnace tailings of 5-10mm into a mixing pot for heating and mixing; pour limestone powder into a mixing pot for heating and mixing; pour SBS modified asphalt into a mixing pot according to the designed amount for heating and mixing; then pour out the evenly mixed OGFC-10 aged steel slag drainage asphalt mixture to form an asphalt mixture specimen.

2. The method for preparing an aged steel slag drainage asphalt mixture OGFC-10 according to claim 1, characterized in that: In the step 1, the free calcium oxide content of the aged converter tailings and the aged electric furnace tailings is less than 3%.

3. The method for preparing an aged steel slag drainage asphalt mixture OGFC-10 according to claim 1, characterized in that: The particle size of the converter tailings is no more than 5 mm, and the particle size of the electric furnace tailings is 5-10 mm.

4. The method for preparing an aged steel slag drainage asphalt mixture OGFC-10 according to claim 1, characterized in that: The gradation design in step 2 is as follows: The pass rate of 13.2mm sieve hole is 100%; the pass rate of 9.5mm sieve hole is 90%~100%; the pass rate of 4.75mm sieve hole is 50%~70%; the pass rate of 2.36mm sieve hole is 10%~22%; the pass rate of 1.18mm sieve hole is 6%~18%; the pass rate of 0.6mm sieve hole is 4%~15%; the pass rate of 0.3mm sieve hole is 3%~12%; the pass rate of 0.15mm sieve hole is 3%~8%; the pass rate of 0.075mm sieve hole is 2%~6%.

5. The method for preparing an aged steel slag drainage asphalt mixture OGFC-10 according to claim 1, characterized in that: In the step 3, limestone not exceeding 3 mm, aged converter tailings not exceeding 5 mm, basalt of 3-5 mm, basalt of 5-10 mm, aged electric furnace tailings of 5-10 mm, and limestone powder are placed in an oven for drying according to the designed amount at a temperature of 105° C. for 2 hours; SBS modified asphalt is placed in an oven for heating and softening at a heating temperature of 165° C. for 2 hours; limestone not exceeding 3 mm, basalt of 3-5 mm, and basalt of 5-10 mm are placed in a mixing pot. Heat and mix for 15s, and set the mixing pot temperature to 165℃; pour aged converter tailings not exceeding 5mm and aged electric furnace tailings of 5-10mm into the mixing pot and heat and mix for 20s, and set the mixing pot temperature to 165℃; pour limestone ore powder into the mixing pot and heat and mix for 5s, and set the mixing pot temperature to 165℃; pour SBS modified asphalt according to the designed amount into the mixing pot and heat and mix for 60s, and set the mixing pot temperature to 165℃.

6. An aged steel slag drainage asphalt mixture OGFC-10 prepared by the method according to any one of claims 1 to 5.